2007
DOI: 10.1177/0145482x0710100803
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Brailled Instructional Materials in Texas Public Schools

Abstract: This study investigated the background of personnel who are responsible for transcribing braille in Texas. Most respondents were not certified by the Library of Congress and believed that they had begun their careers less than adequately prepared, yet they rated the quality of the materials that they produced as either excellent or good.Tina S. Herzberg, Ph.D., assistant professor and director, Visual Impairment Program,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This article has reported demographic data for 166 individuals who are responsible for preparing mathematics materials for tactile learners. The participants had various backgrounds and roles, which is similar to the findings of other authors (Allman & Lewis, 1996;Corn & Wall, 2002;Herzberg & Stough, 2007, 2009Rosenblum & Amato, 2004;Wall & Corn, 2002). It was not surprising to find that the amount of lead time the participants were given to prepare mathematics materials for tactile learners was usually two or fewer days.…”
Section: Discussionsupporting
confidence: 82%
“…This article has reported demographic data for 166 individuals who are responsible for preparing mathematics materials for tactile learners. The participants had various backgrounds and roles, which is similar to the findings of other authors (Allman & Lewis, 1996;Corn & Wall, 2002;Herzberg & Stough, 2007, 2009Rosenblum & Amato, 2004;Wall & Corn, 2002). It was not surprising to find that the amount of lead time the participants were given to prepare mathematics materials for tactile learners was usually two or fewer days.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of U.S. states do not have a sufficient number of certified braille transcribers and hence use a variety of alternatively trained personnel for transcribing instructional materials in braille for students . Certified transcribers, noncertified transcribers, volunteers, paraeducators, and teachers of students with visual impairments are all regularly used to transcribe materials (Allman & Lewis, 1996;Herzberg & Stough, 2007; Rosenblum & Amato, 2004;. A continued and perhaps even more critical shortage of braille transcribers is anticipated (American Foundation for the Blind, AFB, n.d.; .…”
mentioning
confidence: 99%
“…The study presented here was part of a larger project that focused on braille transcribing by public school personnel in Texas (Herzberg & Stough, 2007. The first part of the project investigated who transcribed instructional materials into braille and how the materials were prepared (Herzberg & Stough, 2007). An electronic survey of 94 school personnel across Texas found that instructional materials were often transcribed by a variety of personnel who were often not certified by NLS.…”
mentioning
confidence: 99%
“…Examples of accommodations warranting instruction are Braille and assistive technology. Teachers—TVIs and classroom teachers—are also responsible for providing some accommodations such as Braille materials (Herzberg & Stough, 2007), experiential learning (Wild et al, 2013), and increased verbal information during instruction (Rule et al, 2011).…”
mentioning
confidence: 99%